Analysis Human Resources Development of Lecturer Competency at Poltekad Kodiklatad - Setiawibawa, Rachmat (Universitas Dharma Wacana, 2023)
This research investigates and analyzes the competence of lecturers at Poltekad Kodiklatad, a military-related higher education institution. Against the background of global change and technological progress, this research aims to provide a deeper understanding of the actual conditions and challenges faced by lecturers in this context. Through descriptive research methods with a quantitative analysis approach, data was obtained through direct interviews with 50 lecturers. The data analysis process follows an inductive research pattern with interwoven or flowing interactive techniques.The research results show the condition of the Poltekad Kodiklatad and Study Program, as well as the human resources and infrastructure that support them. In measuring human resource satisfaction, the research used a questionnaire with a Likert scale of 1-5. The survey results show that human resource development, especially in developing lecturer competencies, career development and scientific research, received a high assessment. However, there are certain aspects, such as social needs and welfare needs, that show potential for improvement.It is hoped that this research will contribute to the understanding of how to improve the competence of lecturers in the polytechnic environment, especially those related to the military context. The results of this research provide valuable recommendations and input for the development of human resources in the field of military education, with the potential to make a positive contribution to the quality of education at Poltekad Kodiklatad.